Therapeutic and Diagnostic Tactics for Metastases to the Lymph Nodes of the Neck without an Identified Primary Focus - M. I. Sokolova; V. I. Pavlova (Креативная хирургия и онкология)
Introduction. Metastatic squamous cell carcinoma from an unknown primary focus accounts for less than 5 % of malignant tumors in the head and neck. Improving the methods of diagnosis can reduce the incidence of this pathology. Materials and methods. A retrospective analysis of the results of diagnosis and treatment of 59 patients with metastasis to the lymph nodes of the neck without an identified primary focus was performed. The proportion of male patients was 86 % (51/59), female — 14 % (8/59). The average age of patients is 61 years. Squamous cell carcinoma prevailed — 79 % (47/59). Results. Metastatically affected lymph nodes were localized in 92 % of cases at levels II and III. The proportion of patients with stages N2, N3 prevailed — 55 % (abs. 26), 32 % (abs. 15), respectively. Overexpression of the P16 protein in metastatically affected lymph nodes was detected in 70 %, PDL1 in 48 %, and EpsteinBarr virus (EBV) in 6 %. Ipsilateral diagnostic palatine tonsillectomy of an apparently unchanged tonsil was performed in 15 % (9/59) of cases, revealing the primary site in one instance. Of the special treatment methods, complex and combined treatment prevailed — 55 % (abs. 26). Radiation therapy in an independent version was performed by 48 % of patients, while 76 % received the full course (abs. 16). Combined treatment (a course of Radiation therapy followed by chemotherapy) — in 7 % (abs. 3) 20 % of patients received polychemotherapy. Palliative immunotherapy (pembrolizumab 200 mg IV — 5 courses) was given to 1 patient. The average life expectancy was higher with complex treatment — it was 60 months (95 % CI 43.5–76.4), the median survival is 60 months. Discussion. The main methods of treatment of patients with metastases of squamous cell carcinoma without were radiation therapy in an independent version, as well as complex treatment. Ipsilateral diagnostic palatine tonsillectomy of an apparently unchanged tonsil was performed in 15 % (abs. 9), and allowed to identify the primary focus in 1 case.Conclusion. Metastasis to the lymph nodes of the neck without remains an urgent interdisciplinary problem. Prospective multicenter studies are required to improve and optimize the algorithms for diagnosis and treatment of these patients.